Independent audit as a strategic tool to reduce the information asymmetry on the market - Kustienė, Aurelija (Buhalterinės apskaitos teorija ir praktika, 2014)
This paper analyses the problems of information asymmetry in the market. The research problem: how to minimize the limitations of the influence of user information, and the quality of market participants who use financial statements provide information, awareness. The aim of the research is to reveal the independent audit role in reducing information asymmetry in the market. This objective was achieved by analysing the theories of economic: information asymmetry, signalling and agency theories. Based on the analysis of economic theories and using a logical method of analysis it was concluded that the information asymmetry in the market can be reduced by a strategic tool for the independent audit.